(untitled) (Minerva. Revista de Filología Clásica, 2019)
The Homeric βάλλω does not conceal two different lexical items. Both βάλλω1 ’throw and hit’ (with Acc. of the projectile and directive or locative expressions) and βάλλω2 ’hit’ (with Acc. of the reached goal and Dat. of the projectile) are contextual variants of one and the same verb ’hit by throwing’. The choice between both representations depends on the lexical reference of the goal: βάλλω1 is regularly employed when the goal refers to a place, βάλλω2 when it refers to a human being. The choice reflects the special relevance of human beings in the sentence: the highest semantic functions are attached to animates, and especially to human beings.